Nationalism and the Ottoman-Arab Dynamic: From Cultural Renaissance to Political Revolt - Nasir Hassan Wani (Penerbit Hellow Pustaka, 2024)
This paper delves into the intricate relationship between the Ottoman Empire and its Arab Muslim subjects amidst the backdrop of rising nationalist sentiments during the late 19th and early 20th centuries. It traces the historical evolution of Arab nationalism, examining its cultural origins and political dimensions, while also dissecting the Ottoman administration's response to nationalist aspirations. Through an analysis of historical documents, scholarly works, and contemporary accounts, the study illuminates how nationalist movements reshaped the political, social, and cultural dynamics within the empire, leading to increased tensions between the central government and Arab nationalists. The paper highlights key events such as the Tanzimat reforms and the Young Turk Revolution, which exacerbated these tensions, culminating in the Arab Revolt of 1916 supported by the British. It also explores the impact of World War I on Ottoman-Arab relations and the subsequent dissolution of the empire, as reflected in treaties like the Treaty of Sèvres and the Treaty of Lausanne, which paved the way for the establishment of modern Arab states under European mandates. Through a comprehensive examination of historical sources and scholarly literature, the paper elucidates the multifaceted nature of nationalism's influence on the Ottoman Empire's relationship with its Arab Muslim subjects, underscoring its profound and enduring significance in shaping the modern Middle East.